(untitled) (Global Journal of Science Frontier Research, 2019)
The aim of this study is to assess urban cooling island effects of Jabi Lake Reservoir, Abuja on its surrounding microclimate using geospatial techniques. To achieve this, the UCI effects of Jabi Lake Reservoir on surrounding microclimate were analyzed by applying UCI indices such as UCI scale, temperature difference, and UCI intensity. The thermal bands 10 and 11 of Lands at 8 OLI/TIRS satellite imageries acquired on 29th November 2017 were utilized in retrieving LST data while high resolution (0.7 m) QuickBird imagery acquired in 2017 was used to map Jabi Lake Reservoir. Five land use categories were identified and classified within the study area which showed that bare surface covered 607.33 sq.km; water body, 1.32 sq.km; built-up, 281.47 sq.km; vegetation, 453.27 sq.km; and rock outcrop, 114.33 sq.km. It was shown that NDVI and buffer distances from Lake boundary exhibited a strong negative relationship with correlation coefficient, R = -0.94. Jabi Lake Reservoir recorded the lowest surface temperature with a mean value of 24.59°C.